Classification of factorable surfaces in the pseudo-galilean space - Aydin, Muhittin Evren; Ogrenmis, Alper Osman; Ergut, Mahmut (University of Zagreb, Faculty of Mining, Geology and Petroleum Engineering, 2015)
In this paper, we introduce the factorable surfaces in the pseudo-Galilean space G13 and completely classify such surfaces with null Gaussian and mean curvature. Also, in a special case, we investigate the factorable surfaces which fulfill the condition that the ratio of the Gaussian curvature and the mean curvature is constant in G13. © 2010 Mathematics Subject Classification.
Keywords: Factorable surface; Gaussian curvature; Mean curvature; Minimal surface; Pseudo-Euclidean plane; Pseudo-Galilean space